EFL Vocabulary Tests - Meara, Paul.; Wales Univ., Swansea. Univ. Coll. Centre for Applied Language Studies ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1992)
This volume contains a set of experimental English language vocabulary tests designed to be used with learners of English as a Second Language (ESL). The tests are graded into 6 levels of difficulty and there are 20 tests at each level. Teachers can use the tests to provide a rough lexical profile of individual students, or to monitor the progress of students whose lexical profile has already been established. The tests are based on work carried out at the Centre for Applied Language Studies at University College Swansea (Wales). The tests differ from conventional vocabulary tests in that responses are not given in a multiple choice format. Instead, the testee decides whether he knows the word or not and marks the word with a Y for yes or an N for no. A special feature of these tests is that each of them includes a number of non-existent, imaginary words, which supply an automatic check on how much guessing a testee is doing. An average testee can complete five or six of these tests in less than half an hour. The tests have not yet been validated with large populations of learners of ESL. The tests have been used with a range of learners who were native speakers of Indo-European languages, mainly French, Spanish, Italian, and the Germanic languages. (JP)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Difficulty Level; English (Second Language); Foreign Countries; Indo European Languages; Language Tests; Test Format; Test Use; Testing; Vocabulary Skills; Tests/Questionnaires.